The contribution of information technology to improving the performance of employees in sports institutions (Field study at the Youth and Sports Directorate of Skikda State( - Krika, Mohammed; Rachef , Abdel Momen (sports creativity, 2024)
Our goal, through this study, which includes the title of the contribution of information technology to improving the performance of workers in the Directorate of Youth and Sports of Skikda State, is to reveal the extent to which information technology, in its three dimensions (hardware, computers, software, networks), contributes to improving the performance of workers in the Directorate of Youth and Sports of Skikda State. The study was conducted on a simple random sample of 35 workers out of 52 employees in the directorate. We relied on the descriptive approach and the questionnaire as a tool for collecting data. The study reached the following results: Information technology contributes to a moderate degree in improving the performance of employees with an arithmetic mean of (3.385) and a standard deviation of (1.172). Devices and computers also contribute to improving the performance of employees in sports institutions to a high degree, with a mean of (3.452) and a standard deviation of (0.399). Software also contributes to improving the performance of workers in sports institutions to a high degree, with a mean of (3.657) and a standard deviation of (0.657). In addition, networks contribute to improving the performance of employees in sports institutions to a moderate degree, with an arithmetic mean of (3.12) and a standard deviation of (0.234.)